Imaging and Programming Based Computation of Logistic Package Volumes Application on Automatic Mail Machines - Prayitno, Adhy; Shiddiq, Minarni; Arief, Dodi Sofyan; Mirdanies, Midriem; Ayunita, Dyna (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
At present the determination of weight and volume has been widely used to assist in the process of determining costs for freight forwarding services. Shipping costs are determined by the weight of the goods, but the weight of the goods consists of two types, namely actual weight and volume weight. The weight of the weighing will be used directly if the item or box is small, but if the item is large but the weight is real then the weight of the volume will be used. Algorithms that combine triangulation and 2D measurement techniques can be used to build 3D surfaces so they can measure the volume of a product. Determination of volume in the optical scoring system can be done using the laser triangulation method and the area of 2D image measurement, then using a computer algorithm to get the results of 3D images to determine the volume of the object. The calculation process used in this study uses MATLAB software. MATLAB is the most efficient software for matrix-based numerical calculations and is widely used in mathematical calculations, development and algorithms, programming modeling, prototyping and simulation, data analysis, exploration and visualization, numerical and statistical analysis, and technical application development. The results of the study using MATLAB include students becoming more interested in learning and more independent in learning mathematics, can visualize data graphically to help analyze the data analyzed, and help in modeling the characteristics of variations in fuel mixtures which include density, viscosity, dynamic and kinematic viscosity.